Restorative effects of Momordica charantia extract on cerebellar GFAP and NGF expression in pregnant diabetic rats and their offspring - Amoura M. Abou-El-Naga; Hend Abd EL-Halim Mansour; Mamdouh R. El-Sawi; Mai Alaa El-Dein; Yasmin M. Tag; Reham A. Ghanem; Manar A. Shawki (PLoS ONE, 2025)
Maternal diabetes mellitus is linked to neurobiological and cognitive impairments, increasing the risk of brain and cerebellar defects in diabetic pregnant rats and their offspring. Momordica charantia (bitter melon) possesses antidiabetic properties due to its bioactive compounds, including phenolics, alkaloids, proteins, steroids, inorganic compounds, and lipids. Forty pregnant rats were randomly assigned to four groups: control; M charantia (BM); diabetic (DM); and diabetic treated with M charantia (BM+DM). Diabetic maternal rats showed significantly elevated serum glucose, insulin, leptin, and homeostasis model assessment of insulin resistance (HOMA-IR) levels, with a concomitant decrease in insulin sensitivity check index (QUICKI), glucose transporter 4 (GLUT4), adenosine monophosphate-activated protein kinase (AMPK), acetylcholine (ACh), and dopamine. Oxidative stress markers in cerebellar tissue indicated increased malondialdehyde (MDA) and decreased glutathione (GSH) levels. Cerebellar tissue analysis revealed significantly reduced superoxide dismutase (SOD), catalase (CAT), B-cell lymphoma 2 (Bcl-2), and nerve growth factor (NGF), while Bcl-2-associated X protein (BAX) and glial fibrillary acidic protein (GFAP) were elevated. Histological and ultrastructural analysis of the diabetic maternal cerebellum showed moderate vacuolation of the neuropil in all cerebellar cortical layers, along with Purkinje cell degeneration and necrosis, including Nissl substance loss. Offspring of diabetic mothers exhibited multifocal Purkinje cell loss, empty baskets, and cerebellar cortical dysplasia with abnormal tissue development and organization. In conclusion, M. charantia supports central nervous system health in diabetic pregnant rats and their offspring by enhancing antioxidant markers, regulating GFAP and NGF, and mitigating apoptosis, ultimately improving cerebellar pathology and neural development.